A Novel Single-Strand RNAi Therapeutic Agent Targeting the (Pro)renin Receptor Suppresses Ocular Inflammation - Atsuhiro Kanda; Erdal Tan Ishizuka; Atsushi Shibata; Takahiro Matsumoto; Hidekazu Toyofuku; Kousuke Noda; Kenichi Namba; Susumu Ishida (Elsevier, 2017)
The receptor-associated prorenin system (RAPS) refers to the pathogenic mechanism whereby prorenin binding to the (pro)renin receptor [(P)RR] dually activates the tissue renin-angiotensin system (RAS) and RAS-independent intracellular signaling. Here we revealed significant upregulation of prorenin and soluble (P)RR levels in the vitreous fluid of patients with uveitis compared to non-inflammatory controls, together with a positive correlation between these RAPS components and monocyte chemotactic protein-1 among several upregulated cytokines. Moreover, we developed a novel single-strand RNAi agent, proline-modified short hairpin RNA directed against human and mouse (P)RR [(P)RR-PshRNA], and we determined its safety and efficacy in vitro and in vivo. Application of (P)RR-PshRNA in mice caused significant amelioration of acute (uveitic) and chronic (diabetic) models of ocular inflammation with no apparent adverse effects. Our findings demonstrate the significant implication of RAPS in the pathogenesis of human uveitis and the potential usefulness of (P)RR-PshRNA as a therapeutic agent to reduce ocular inflammation.